Penataan Manajemen Sumber Daya Aparatur Pemerintah Daerah Kabupaten Gorontalo - Muhamad Reza Tjokra; Nandar Alfian Gani; Novita B. Mukdin; Nirmala Afrianti Sahi; Sarfan Tabo (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The arrangement of civil servant resource management is a key factor in improving the effectiveness of government administration and the quality of public services at the regional level. This study aims to analyze the arrangement of civil servant resource management in the Regional Government of Gorontalo Regency. This study uses a qualitative approach with a case study method. Data collection was conducted through observation, in-depth interviews, and documentation with key informants, the Head and employees of the Civil Service and Human Resources Development Agency of Gorontalo Regency, as well as supporting informants from one of the sub-district heads within the Regional Government of Gorontalo Regency. Data validity was tested through triangulation techniques, while data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The analysis of civil servant resource management refers to Sedarmayanti’s theory with a focus on three indicators, namely employee placement according to expertise, a clear and planned career pattern, and employee recruitment according to procedures. The results of the study indicate that the arrangement of civil servant resource management in the Regional Government of Gorontalo Regency has generally been implemented well. However, there are still obstacles such as the lack of regional head regulations regarding career patterns of civil servants and the limited number of employees that do not fully match the needs of the organization.